Developing Augmented Reality-based Learning Media to Improve Student Visual Spatial Intelligence - Wahyudi, Urip Muhayat Wiji; Arwansyah, Yanuar Bagas (Universitas Negeri Semarang, 2019)
This article illustrates an effort to create a learning media based on Augmented Reality (AR) to improve student visual spatial intelligence. This type of intelligence is important for student to understand such subjects or topics like spaces, because to completely understand the image student should imagine the object’s shape and space. The lack of learning media in many schools caused the lack of student understanding toward the topic. According to the problem above, this research employing Research & Development (R & D) approach to develop AR-based learning media to facilitate 6th grade student to learn solar system more visually. The post-test has shown that there is an increased number of student visual spatial intelligence, especially on solar system topic. So, it can be concluded that AR-based learning media has huge potential to facilitate student to learn such topics related to space and the like. Abstrak Artikel ini menggambarkan upaya pengembangan media pembelajaran berbasis Augmented Reality (AR) untuk meningkatkan kecerdasan spasial visual siswa. Jenis kemampuan ini penting bagi siswa untuk memahami subjek atau topik yang berkaitan dengan konsep ruang, karena untuk sepenuhnya memahami gambar, siswa harus membayangkan bentuk dan ruang dari objek tersebut. Kurangnya media pembelajaran di banyak sekolah menyebabkan kurangnya pemahaman siswa tentang topik tersebut. Berdasarkan masalah di atas, penelitian ini menggunakan pendekatan Research & Development (R & D) untuk mengembangkan media pembelajaran berbasis AR untuk memfasilitasi siswa kelas 6 belajar tata surya secara lebih visual. Hasil post-test telah menunjukkan bahwa terdapat peningkatan kemampuan spasial visual siswa, terutama pada topik tata surya. Jadi, dapat disimpulkan bahwa media pembelajaran berbasis AR memiliki potensi besar untuk memfasilitasi siswa mempelajari topik-topik yang berkaitan dengan ruang dan sejenisnya.